PHB2 promotes colorectal cancer cell proliferation and tumorigenesis through NDUFS1-mediated oxidative phosphorylation - Lin Ren; Li Meng; Jing Gao; Mingdian Lu; Chengyu Guo; Yunyun Li; Ziye Rong; Yan Ye (Cell Death and Disease, 2023)
Abstract The alteration of cellular energy metabolism is a hallmark of colorectal cancer (CRC). Accumulating evidence has suggested oxidative phosphorylation (OXPHOS) is upregulated to meet the demand for energy in tumor initiation and development. However, the role of OXPHOS and its regulatory mechanism in CRC tumorigenesis and progression remain unclear. Here, we reveal that Prohibitin 2 (PHB2) expression is elevated in precancerous adenomas and CRC, which promotes cell proliferation and tumorigenesis of CRC. Additionally, knockdown of PHB2 significantly reduces mitochondrial OXPHOS levels in CRC cells. Meanwhile, NADH:ubiquinone oxidoreductase core subunit S1 (NDUFS1), as a PHB2 binding partner, is screened and identified by co-immunoprecipitation and mass spectrometry. Furthermore, PHB2 directly interacts with NDUFS1 and they co-localize in mitochondria, which facilitates NDUFS1 binding to NADH:ubiquinone oxidoreductase core subunit V1 (NDUFV1), regulating the activity of complex I. Consistently, partial inhibition of complex I activity also abrogates the increased cell proliferation induced by overexpression of PHB2 in normal human intestinal epithelial cells and CRC cells. Collectively, these results indicate that increased PHB2 directly interacts with NDUFS1 to stabilize mitochondrial complex I and enhance its activity, leading to upregulated OXPHOS levels, thereby promoting cell proliferation and tumorigenesis of CRC. Our findings provide a new perspective for understanding CRC energy metabolism, as well as novel intervention strategies for CRC therapeutics.